The Effect of Green Banking Disclosure, Leverage, and Corporate Governance on Islamic Banks’ Financial Performance - Maharani, Reza Putri; Yuningrum, Heny; W, Eka Harisma (MALIA: Journal of Islamic Banking and Finance, 2026)
In recent years, Islamic Commercial Banks in Indonesia have faced increasing pressure to enhance financial performance while complying with sustainability principles and sound corporate governance. The implementation of green banking practices, effective leverage management, and good corporate governance (GCG) are considered crucial factors in maintaining competitiveness and long-term stability in the Islamic banking industry. This study aims to analyze the effect of Green Banking Disclosure, Leverage, and Good Corporate Governance (GCG) on the financial performance of Islamic Commercial Banks (ICBs) in Indonesia during the 2020–2023 period. This study employs a quantitative research design with an explanatory approach. Data were collected using the documentation method, consisting of financial statements and annual reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the 2020–2023 period. Data analysis was conducted using panel data regression techniques with statistical software. The results show that Green Banking Disclosure does not have a significant effect on the financial performance of Islamic Commercial Banks, as indicated by a significance value above 0.05. In contrast, Leverage and Good Corporate Governance (GCG) have a negative and significant effect on financial performance. Simultaneously, Green Banking Disclosure, Leverage, and GCG significantly affect financial performance. These findings indicate the importance of effective leverage management and strong corporate governance in improving the financial performance of Islamic Commercial Banks.